Baseline hs‐CRP predicts hypertension remission in metabolic syndrome. (3rd June 2019) - Carbone, Federico; Elia, Edorado; Casula, Matteo; Bonaventura, Aldo; Liberale, Luca; Bertolotto, Maria; Artom, Nathan; Minetti, Silvia; Dallegri, Franco; Contini, Paola; Verzola, Daniela; Pontremoli, Roberto; et al.
Abstract: Background: Inflammation, overweight and other cardiovascular risk factors might negatively impact on hypertension remission in metabolic syndrome (MetS), independently of the pharmacological treatment. Here, the potential influence of systemic inflammation (assessed by serum high‐sensitivity C‐reactive protein [hs‐CRP]) on hypertension remission will be investigated in a cohort of hypertensive patients with MetS. Material and Methods: Hypertensive patients with MetS (n = 100) were enrolled, treated under current behavior/dietary/pharmacological recommendations and followed up for 12 months. All patients received medications and nutritional advice based on Mediterranean‐like dietary pattern in addition to psychological and physical activity counselling. At baseline (T0), 6 (T1) and 12 (T2) months of follow‐up, clinical data, haematological and biochemical profiles and serum hs‐CRP were measured. Results: As compared to T0, at T2 patients displayed improvements in anthropometric and metabolic profiles. At T2, the hypertension remission rate was 13.0%. Serum hs‐CRP did not change overtime in the overall cohort. Surprisingly, patients who experienced hypertension remission were less treated with antihypertensive drugs, but developed a weak improvement in anthropometric measures during follow‐up. The hypertension remission group had lower baseline levels of hs‐CRP as compared to non‐remission. Low baseline hs‐CRP (<2 µg/mL, cut‐off value identified by ROC curve) predicted hypertension remission, independently of antihypertensive treatment implementation, baseline systolic blood pressure and waist circumference improvement. Conclusions: Remission of hypertension in MetS is independently associated with baseline low CRP levels, which might suggest a critical role for inflammation in sustaining high blood pressure levels.